Stress relaxation behavior of graphene-epoxy nanocomposites: Effects of graphene fraction, strain levels, and temperature - Acar, Alperen; Bakbak, Okan; Colak, Ozgen (SAGE PUBLICATIONS LTD, 2025)
In this study, strain level and temperature-dependent stress relaxation behavior of neat epoxy and graphene-epoxy nanocomposites are experimentally investigated. Tests are performed for neat epoxy, graphene-epoxy nanocomposite with content of 0.1 wt% and 0.5 wt% graphene. To determine the effect of strain levels on relaxation behavior, three constant strain levels are chosen: 3.16%, 7.15%, and 35.5%. Those strain levels are chosen to correspond to different zones on the stress-strain curves as: viscoelastic region, yield region, and visco-plastic region. Results have shown that with the addition of 0.1 wt% graphene, relaxation modulus improved 41% at 3.16% constant strain. The effect of graphene is less effective at high strain values: for 7.15% strain, the change in relaxation modulus is 32%, and at 35.5 %strain, the change is 21.25%. In addition, tests are performed for three temperature values: 23, 65, and 120 degrees C to determine the effect of temperature on the relaxation behavior. As expected, nano composition has an improved effect on the stress relaxation behavior. An increasing temperature increases the stress relaxation values. At room temperature (for 7.15% constant strain level) the drop in relaxation modulus for neat epoxy is 32%, this value drops to 22% with the addition of 0.1 wt% graphene. At 65 degrees C, the rate of decrease in modulus with the addition of graphene is almost unchanged. At 120 degrees C, the relaxation performance of the material slightly decreases. Therefore, as a novel result of the research, it is determined through the conducted experiments that increasing temperature lessens the improvement effect of graphene composition on the stress relaxation behavior.
Keywords: Graphene nanocomposites; stress relaxation; thermo-viscoelastic behavior; CREEP; Materials Science; Polymer Science